PENDIDIKAPENDIDIKAN KARAKTER PERSPEKTIF IBNU SINA (RELIGIUS RASIONAL) - Hambali Alman Hambali; Fikri Alwi Nasution (PAI RAFAH, 2020)
Life in a fast-global era demands various changes, be it changes in basic education. The changes include changes from the perspective of the life of local communities to global society, changes in social cohesion to democratic participation, and changes from economic growth to human development. In facing the various changes and developments in the above problems, it is important to make arrangements for the education system as a whole and comprehensively, especially with regard to the quality of education and its relevance to the needs of society and the times. So that social change is needed which gives direction that education is a basic approach in the change process. The purpose of this research is to find out how Ibn Sina's perspective education in character education, according to Ibn Sina's educational thinking, aims that education is not only a transfer of knowledge but also a transfer of values.This study using a type of library research with a qualitative descriptive analysis method. In this study, the authors wanted to research and analyze the development of techniques and instruments for the assessment of technology-based aspects of knowledge. Data collection using documentation. Data analysis used a qualitative descriptive method, using literature research.From the results of the explanation of the educational perspective above, that according to Ibn Sina education is directed at potential and is based on good strategies, methods, curriculum. With the aim, a person's potential grows and will develop according to how we teach the education given. He revealed that human character grows and develops if we provide education in accordance with the potentials of students. Ibn Sina views that education as a means to make students noble and virtuous, not just knowledge.